Android-Based Dental Disease Education Model in Improving Adolescent Dental Health Maintenance Skills - Julia Dance Setyowati; Ulliana Ulliana (Center of Excellent (Pusat Unggulan Iptek), 2023)
Background: Dental and oral health is critical to pay attention to in addition to other general body health. Students who experience caries and gingivitis in industrialized countries by 60-90%. Efforts to overcome these problems through the UKGS program. However, the program still has obstacles, including the health education media provided is still conventional. Educational media that are currently developing among adolescents are technology-based. Purpose: Produce an android-based dental and oral disease education model that effectively improves adolescent dental health behaviour. Methods: Research and Development (R&D) and model testing using a quasi-experiment design (pre and post-test with control group design), model feasibility measurement instruments and skills using a questionnaire. Data were tested using the Wilcoxon test and the Mann-Whitney test. The study subjects were divided into two groups, namely the intervention group of 45 children and the control group of 45 children. Result: Android-based education model is feasible as a medium for dental health education (p = 0.004) and effective in improving adolescent skills (p = 0.000). Conclusion: Android-based education can potentially improve adolescents' dental and oral health maintenance skills.